PERAN GURU PKN DALAM MENGINTERNALISASI NILAI-NILAI PANCASILA SEBAGAI PENGUATAN KARAKTER DEMOKRASI PADA SISWA DI SDN 14 RIANIATE - Sadrah Mesak Manik; Yakobus Ndona; Daulat Saragi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to estimate the value of democratic character building in elementary school students through a qualitative descriptive approach with the research object at SDN 14 Rianiate. Data were collected through observation, interviews, and documentation to explore the role of education in shaping a generation committed to national values, possessing a spirit of nationalism, and being able to appreciate differences and prioritize common interests. The results of the study indicate that the development of democratic character can be realized through a holistic Pancasila learning strategy, active teacher involvement, and real activities such as democracy day that train students to get used to deliberation in making joint decisions and foster an attitude of tolerance and awareness of togetherness.